Transient Thermomechanical Simulation of 7075 Aluminum Contraction around a SiO(2) Microparticle - Tamayo-Meza, Pedro Alejandro (Materials (Basel), 2020)
One important challenge that faces the metallurgic industry turns around the constant increment in the mechanical resistance of certain finished products. Metallurgic advantages can be obtained from the inclusion of microparticles in metallic materials, but this inclusion involves complex challenges as the internal stress distribution can be modified. In this work, the simulation of a cooling sequence in 7075 aluminum with a SiO(2) microparticle is presented. Two models of two-dimensional (2D) type were constructed in ANSYS(®)2019 with circular and oval shape microparticles located inside the aluminum. Both models were subjected to the same thermomechanical transient analysis to compare the remaining stress distributions around the microparticles after the thermal load and to observe the effect of the geometrical shape. The results show remaining stresses increased in the oval model as a consequence of the geometrical shape modification. After applying a tension load in the analyzed specimens, shear stress concentrations were observed with a higher magnitude around the covertex of the oval shape. The results can be very useful for the creation of materials with controlled remnant stress located in specific or desired locations in the matrix.